Melt onset over Arctic sea ice controlled by atmospheric moisture transport. Issue 12 (28th June 2016) - Mortin, Jonas; Svensson, Gunilla; Graversen, Rune G.; Kapsch, Marie‐Luise; Stroeve, Julienne C.; Boisvert, Linette N.
Abstract: The timing of melt onset affects the surface energy uptake throughout the melt season. Yet the processes triggering melt and causing its large interannual variability are not well understood. Here we show that melt onset over Arctic sea ice is initiated by positive anomalies of water vapor, clouds, and air temperatures that increase the downwelling longwave radiation (LWD) to the surface. The earlier melt onset occurs; the stronger are these anomalies. Downwelling shortwave radiation (SWD) is smaller than usual at melt onset, indicating that melt is not triggered by SWD. When melt occurs early, an anomalously opaque atmosphere with positive LWD anomalies preconditions the surface for weeks preceding melt. In contrast, when melt begins late, clearer than usual conditions are evident prior to melt. Hence, atmospheric processes are imperative for melt onset. It is also found that spring LWD increased during recent decades, consistent with trends toward an earlier melt onset. Key Points: Humid air masses trigger Arctic sea ice melt by means of longwave radiation Melt preconditioning of the sea ice surface prior to melt onset Trends toward earlier melt onset linked to positive trends of longwave radiation in spring